1964
DOI: 10.3758/bf03342974
|View full text |Cite
|
Sign up to set email alerts
|

Impedance-time functions in the white rat with chronic body electrode implants

Abstract: AhstractFour male albino rats were implanted with chronic body shock electrodes. Impedance measurements were made at a low impressed voltage over a 38-day period following implantation. Impedance was found to increase significantly as a function of time since implantation, although the absolute magnitude of the rise varied among animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1965
1965
1965
1965

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The several problems associated with presentation of shock through an electrified grid floor (England, 1964) have lead to the development and increasingly successful use of implanted electrodes in various species (Azrin, 1959;Silver et al, 1964). We have found that a nonavoidable and consistent shock can also be delivered to rats through a small metal harness which can be attached before each conditioning session.…”
Section: Introductionmentioning
confidence: 99%
“…The several problems associated with presentation of shock through an electrified grid floor (England, 1964) have lead to the development and increasingly successful use of implanted electrodes in various species (Azrin, 1959;Silver et al, 1964). We have found that a nonavoidable and consistent shock can also be delivered to rats through a small metal harness which can be attached before each conditioning session.…”
Section: Introductionmentioning
confidence: 99%